Pedoman Menentukan Daerah Cuaca Buruk Bagi Para Nahkoda - Mochamad Chaeran; Harcici Harcici (Dinamika Bahari, 2020)
Current weather conditions undergo a very significant change, given that it does not rule out the possibility that there are still many captains often trapped in bad weather areas even though the navigation system is quite adequate, this is due to the fact that there are still many captains not paying attention to weather news in the form of weather charts that show bad weather areas and sunny weather areas. For this reason the captain needs to learn, knowing the symbols of bad weather areas is expected to not get stuck in sailing in bad weather areas.